Proteomic Insights Into Susceptibility and Resistance to Chronic-Stress-Induced Depression or Anxiety in the Rat Striatum - Cai, Xiao; Yang, Chen; Chen, Jin; Gong, Weibo; Yi, Faping; Liao, Wei; Huang, Rongzhong; Xie, Liang; Zhou, Jian (Frontiers in Molecular Biosciences, 2021)
Chronic stress is one of the most key factors for the onset of anxiety and depression disorders. Yet, the stress-induced common and unique molecular basis of the two psychiatric disorders is not fully known and still needs to be explored. Previously, we employed a chronic mild stress (CMS) procedure to induce a rat model including depression-susceptible (Dep-Sus), anxiety-susceptible (Anx-Sus) and insusceptible (Insus) cohorts. In this work, we continuously analyzed the striatal proteomes of the three stressed cohorts by use of comparative proteomics and bioinformatics approaches. Through isobaric tags for relative and absolute quantitation (iTRAQ)-based analysis, 386 abnormally-expressed proteins in total were identified. These deregulated proteins were involved in various biological functions and significant pathways that were potentially connected with resistance and susceptibility to CMS-caused anxious-like or depressive-like behaviors, and hence could act as suggestive protein targets. The further parallel reaction monitoring-based independent investigation showed that alterations in Pak5, Dgkg, Scn4b, Rb1cc1, and Acin1; Ggps1, Fntb, Nudt19, Ufd1, and Ndufab1; Dnajb12, Hbb2, Ap2s1, Ip6k1, and Stk4 were specifically connected with Dep-Sus, Anx-Sus, or Insus groups, respectively, potentially indicating that the identical CMS treatment resulted in the different changes in the striatal protein regulations. Overall, our current proteomics study of the striatum provided an important molecular foundation and comprehensive insights into common and specific deregulations correlated with pathophysiological mechanisms that underlie resistance and susceptibility to chronic-stress-induced anxiety or depression.